PERUBAHAN TRADISI MENANAM PADI DI DESA KEPALA PULAU KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Peri Pernanda; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the Kepala Pulau village Kuantan Hilirsubdistrict, Kuantan Singingi Regency. The purpose of this study is the first tofind out what kind of a tradition in the Kepala Pulau village community to growrice. The second objective is to determine what changes occur in the tradition ofgrowing rice in the Kepala Pulau village community. The third goal is todetermine what are the factors that cause changes in the tradition of growing ricein the Kepala Pulau village community. Analyzing the data in this study usingQualitative Research Methods. Qualitative Research Methods This is an analysisthat seeks to provide a detailed picture of reality based on facts obtained from thefield and also supported by the data in order to support the primary and secondarydata exist. Qualitative research is presented in the form of words from theinterview with the author of the respondents that describe the specificcircumstances of the people in the Kepala pulau village about the tradition ofplanting rice, the changes that occur in the tradition of growing rice and thefactors that cause changes in the tradition of growing rice in the Kepala Pulauvillage community. The results of field research shows that there is occurrence ofsignificant changes in the tradition of growing rice in the Kepala Pulau villagecommunity even the traditions that have been around since the former in theplanting of rice has been lost. It is caused by several factors that influence thechanges that occur in the tradition of growing rice that is the internal factors andexternal factors.Keywords : Tradition of planting rice, Changes